The family therapy treatment planner with DSM-5 updates - Dattilio, Frank M.; Jongsma, Arthur E., Jr; Davis, Sean D. (Practice planners, 2014)
This timesaving resource features:Treatment plan components for 40 behaviorally based presenting problemsOver 1,000 prewritten treatment goals, objectives, and interventions-plus space to record your own treatment plan optionsA step-by-step guide to writing treatment plans that meet the requirements of most accrediting bodies, insurance companies, and third-party payorsIncludes new Evidence-Based Practice Interventions as required by many public funding sources and private insurers PracticePlanners® THE BESTSELLING TREATMENT PLANNING SYSTEM FOR MENTAL HEALTH PROFESSIONALS The Family Therapy T
Keywords: Family psychotherapy; Family relations